Upaya Kerjasama Pemerintah Indonesia – Filipina dalam Memberantas Kegiatan IUU-Fishing di Perbatasan Keduan Negara Khususnya Laut Sulawesi 2014-2016 - Exellano Ramadhan Uno; Ika Riswanti Putranti; Shary Charlotte Pattipeilohy (Journal of International Relations Diponegoro, 2017)
The issue of IUU Fishing in Sulawesi’s waters, occurred because these two countries, Indonesia and Filipina, have direct adjacent yet still haven’t decide on their clear border between the two countries, thus the problem of IUU fishing often occur in the area. This research aims to describe the effort that has been done by Indonesian’s and Philippines Government in eradicating IUU Fishing in the border of the two countries, to be exact in Sulawesi’s water. In this research the writer uses Liberalism Interdependency theory to explain that it is necessary for the two countries to cooperate in solving a problem like IUU Fishing in Sulawesi’s water. The research method used is qualitative which is done by collecting and analysing data, to discover the efforts of the two countries involved in eradicating IUU Fishing in Sulawesi’s water. The result of this research is that Indonesia and the Philippines Governments succeed in executing the plan to eradicate IUU Fishing in Sulawesi’s water, which was done by making bilateral cooperation agreement like MOU and POA. Later on through multilateral agreement of RPOA-IUU which consist of eleven countries that have mutual consent in handling the issue of IUU Fishing, preserve maritime security, and performing joint patrol in Sulawesi’s waters.